Development of Discovery Learning-Based Teaching Modules to Facilitate Mathematical Connection Skills of Phase-F Students in Function Composition and Function Inverse Content - Aprillia, Dea; Maimunah, Maimunah; Kartini, Kartini (FKIP - Universitas Riau, 2025)
This research aims to produce a learning tool with a discovery learning model on function composition and inverse function content that meets valid and practical requirements to facilitate the mathematical connection abilities of F-phase students. This type of research is development research with a 4-D research design. The development that the researchers carried out consisted of four stages, namely: (1) define; (2) design; (3) develop; (4) disseminate. This research produced learning tools in the form of learning tools (Teaching Modules). The results of the research show that the learning tools met the criteria for validity and practicality. The validity of the development product is determined by expert validation with an average percentage of 97.22% in the very valid category. The practicality of the development product was determined by teachers with an average of 96.73%, and students with an average of 91.43% in the very practical category. Thus, the learning tools developed have met valid and practical requirements to facilitate students' mathematical connection abilities.